2006
DOI: 10.1098/rspb.2006.3607
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for presence of maternal mitochondrial DNA in the sperm of Mytilus galloprovincialis males

Abstract: Species of the mussel family Mytilidae have a special mitochondrial DNA (mtDNA) transmission system, known as doubly uniparental inheritance (DUI), which consists of a maternally inherited (F) and a paternally inherited (M) mitochondrial genome. Females are normally homoplasmic for the F genome and males are heteroplasmic mosaics, with their somatic tissues dominated by the maternal and their gonads dominated by the paternal genome. Several studies have indicated that the maternal genome may often be present i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 36 publications
4
69
1
3
Order By: Relevance
“…The long type, on the other hand, was almost identical to that reported by Breton et al (2006). Assignment of the two CR types of M. trossulus to maternal and paternal genomes: The mere fact that a mitochondrial sequence is extracted from a female or a male individual, or even from a female or a male gonad, cannot be used as evidence that it is a maternally or paternally transmitted genome (Venetis et al 2006). The reason is that preparations from male gonads are, more often than not, contaminated by DNA from somatic cells that contain maternal mtDNA, and female tissues may contain small amounts of ''leaked'' paternal mtDNA (Garrido-Ramos et al 1998).…”
Section: Resultssupporting
confidence: 49%
See 3 more Smart Citations
“…The long type, on the other hand, was almost identical to that reported by Breton et al (2006). Assignment of the two CR types of M. trossulus to maternal and paternal genomes: The mere fact that a mitochondrial sequence is extracted from a female or a male individual, or even from a female or a male gonad, cannot be used as evidence that it is a maternally or paternally transmitted genome (Venetis et al 2006). The reason is that preparations from male gonads are, more often than not, contaminated by DNA from somatic cells that contain maternal mtDNA, and female tissues may contain small amounts of ''leaked'' paternal mtDNA (Garrido-Ramos et al 1998).…”
Section: Resultssupporting
confidence: 49%
“…The particular C genome that was sequenced was isolated from sperm that were forced to swim through a Percoll solution for the removal of any debris from somatic cells. In a previous study it was shown that sperm purified in this way contain only paternal mtDNA (Venetis et al 2006). This produced firm evidence that the C genome is paternally inherited.…”
Section: Ussels Of the Genus Mytilus Have The Doublymentioning
confidence: 91%
See 2 more Smart Citations
“…Heteroplasmy can arise when multiple mitochondrial haplotypes are inherited (Kmeic et al, 2006). A classic example of this is doubly uniparental inheritance in mussels, which was shown to generate intra individual cox1 variability in Mytilus L. species by Venetis et al (2006). Heteroplasmy can also arise de novo (typically as somatic variation) through recombination and small-scale mutations derived from replication and repair errors, as well as from the activity of reactive metabolites, in both large genomic and smaller fragments of mitochondrial DNA known as minicircles and sublimons (Kajander et al, 2000;Kmeic et al, 2006;Mao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%